Professional Roles and Stereotypes in the Media and Their Impact on Children - Κουκουμάκα, Ελισάβετ Α. (Education Sciences, 2026)
In this work, professional roles and gender stereotypes in the media are studied, as well as the effect they can have on children aged 7 to 12 years. The quantitative research method is used with a research tool of a structured questionnaire for individual completion which includes three closed type questions. The sample is children aged 7 to 12 years, primary school students in eastern Thessaloniki. Taking into account the research questions, through the research tool information is collected to investigate whether the media act as a source of information on career guidance issues, whether television professions are charged with gender stereotypes and whether through the media these stereotypes are reproduced and adopted by children. Finally, it is studied whether the above stereotypes influence the professional choices of children. The present research does not show that professional roles and gender stereotypes - as presented in the media - influence children's professional choices.